(untitled) (Superficies y Vacío, 2018)
In this work, we report the fabrication of bismuth thin films on glass substrates by Pulsed Laser Deposition. A focused beam of a Nd:YAG laser (9 ns, 10 Hz, 1064 and 532 nm) was utilized to carry out the ablation of a high purity Bi target. The per pulse laser fluence was varied between 0.95 and 1.35 J/cm2, depending on the laser wavelength used. The deposits were characterized by SEM and XRD to analyze the surface morphology of thin films and their crystalline structure, respectively. The SEM micrographs showed differences in roughness, which increased with the laser wavelength. The diffractograms revealed the formation of Bi thin films with a polycrystalline structure or with a preferential orientation, depending on the mean kinetic energy of the plasma ions. The as deposited bismuth thin films were irradiated with a non-focused laser beam at low energies below the ablation threshold. In the laser treated area, it could be observed the formation of periodic structures, known as LIPSS (laser induced periodic surface structures). Depending on the crystallographic structure of the irradiated film, the formed LIPSS showed different characteristics, such as width and shape.